2013
DOI: 10.1111/cote.12065
|View full text |Cite
|
Sign up to set email alerts
|

Clay nanoadsorbent as an environmentally friendly substitute for mordants in the natural dyeing of carpet piles

Abstract: The aim of this work was to assess the possibility of using a bentonite‐type clay as a promising substitute for mordants in the natural dyeing of wool with madder. Wool yarn was treated with nanoclay by using three conventional methods of pretreatment (before dyeing), simultaneous dyeing with madder in the presence of clay, and aftertreatment (after dyeing). Madder was used as a natural source of colorant. The scientific methods employed in this study included Fourier Transform‐infrared spectroscopy, ultraviol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…By comparing the results obtained here with previous studies on natural dyes, it was concluded that metal cations used as mordants are able to provide coordination complexes with wool amino acid groups (NH 2 , COOH) on the one hand and with functional groups of juglone (OH, C=O) on the other, resulting in bridge formation .…”
Section: Resultssupporting
confidence: 68%
“…By comparing the results obtained here with previous studies on natural dyes, it was concluded that metal cations used as mordants are able to provide coordination complexes with wool amino acid groups (NH 2 , COOH) on the one hand and with functional groups of juglone (OH, C=O) on the other, resulting in bridge formation .…”
Section: Resultssupporting
confidence: 68%
“…We also observed a further decrease in L* as the concentration of mordants was increased during the premordanting processes. As a result, we can conclude that premordanting is a very beneficial process for obtaining bright colours in nylon 6 dyed with henna and P. fraxinifolia leaf extracts [41].…”
Section: Effect Of Mordants On Colorimetric Changesmentioning
confidence: 76%
“…The circles in the figure indicate where each dye molecule can interact with nylon 6 and tannic acid. Our previous study of the dyeing of wool with madder extracts showed that wool macromolecular chains interacted with aluminium salt and clay minerals prior to dyeing [30,31,41].…”
Section: Effect Of Mordants On Colorimetric Changesmentioning
confidence: 99%
“…The effectiveness of mordants and other compositions (clays, enzymes) [17,18] and extraction procedures [19] in improving dyeing efficiency and use of waste materials from new sources for dye extraction have been reported [20]. In fact, researchers have provided significant evidence that had led to improvements in fastness and affinity or found new sources of natural dye extracts.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, researchers have provided significant evidence that had led to improvements in fastness and affinity or found new sources of natural dye extracts. The effectiveness of mordants and other compositions (clays, enzymes) [17,18] and extraction procedures [19] in improving dyeing efficiency and use of waste materials from new sources for dye extraction have been reported [20]. As there has been hardly any previous research on the application of plant-based hair dyes, this work is a starting point to introduce a new dyeing agent into the cosmetic industry.…”
Section: Introductionmentioning
confidence: 99%